Maskless ultraviolet projection lithography with a biorepelling monomolecular resist - Jeyachandran, Yekkoni Lakshmanan; Meyerbröker, Nikolaus; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
Here, we describe a universal photolithography setup for the patterning of biorepulsive self-assembled monolayers (SAMs) as well as other monomolecular films. The setup is based on commercial equipment consisting of a computer-controlled digital micromirror device chip combined with a suitable optics and a powerful light-emitting diode (LED) source delivering ultraviolet (UV) light with a wavelength of 375 nm. Digital patterns generated in the computer serve as an input for the chip, which modulates the reflected light accordingly, transferring the pattern to the sample surface. The performance of the setup was demonstrated by UV-induced modification of the nonsubstituted alkanethiolate (NS-AT) SAMs and biorepulsive oligo(ethylene glycol)-substituted AT (OEG-AT) monolayers on Au(111), upon homogeneous illumination of the test samples. Further, both nonspecific and specific templates for the protein adsorption were fabricated in the protein-repelling OEG-AT matrix by either direct writing or using an additional irradiation-promoted exchange reaction with a biotin-terminated AT. These templates were used either for nonspecific adsorption of bovine serum albumin (BSA) or for the specific adsorption of avidin, the latter relying on the interaction with the embedded biotin receptors. The density of the adsorbed protein layers across the patterns could be precisely varied by selection of proper irradiation doses.